Development of criteria for the selection and investigation of PEMFC stacks as components of hybrid energy sources for UGVs - Zarzycki, Mikolaj; Dudek, Magdalena; Razniak, Andrzej; Maslowski, Andrzej; Perski, Arkadiusz; Czupryniak, Rafal (International Conference on Methods and Models in Automation Robot. (Online), 2024)
This paper focuses on developing the methodology for selecting polymer exchange membrane fuel cell (PEMFC) stacks as the main energy source to supply an unmanned ground vehicle (UGV). The first part of the paper presents the experimental investigations of the electrical load profiles recorded for the PIAP PATROL UGV during both vehicle movement and manipulator operation. The numerical simulation of the energy demand profile was performed for various terrains and roads. The 2 kW PEMFC stack is proposed and investigated as an electrochemical energy source to supply the medium-sized tracked vehicle. In addition, the preliminary test of the 2 kW PEMFC stack performance in powering the electric motor while traveling is demonstrated.